Modified Titanium Oxide with Metal Doping as Photocatalyst in Photochemical Water Splitting - Haris Prayudha Setyawan; Okta Suryani (Universitas Nusa Bangsa, 2024)
This article focuses on the modification of titanium oxide (TiO2) using metal doping to improve its photocatalytic activity in photochemical water splitting systems. TiO2 is a widely used photocatalyst, which has a wide band gap energy and rapid recombination of photogenerated electron-hole pairs, thus reducing the efficiency of photochemical water splitting systems. Metal doping, such as Pt, Cu, Fe, and V metals can lower the band gap energy of the photocatalyst, increase the absorption of visible light, and reduce electron-hole recombination. Modified TiO2 shows promising results in photochemical water splitting, utilising a wider range of visible light from the solar spectrum thereby improving the efficiency of the photochemical water splitting system.